1985
DOI: 10.3109/03630268508997037
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Observations on Arabian SS Patients with a Homozygosity or Heterozygosity for a βSChromosome with Haplotype #31

Abstract: Hematological and hemoglobin composition data are presented for seven Arabian SS patients with mild disease and with high Hb F levels varying between 21 and 34%. Four patients were homozygous for a beta S chromosome with a specific haplotype (#31). The data for these four patients were similar to those for three other SS patients (and for five patients reported earlier, Ref. 2) who were heterozygous for the same beta S chromosome (#31) and for a beta S chromosome with another haplotype (mainly #19). These data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Historically, five major b-haplotypes, including Senegal, Benin, Central African Republic (Bantu), Cameroon, and Asian (Indian/Saudi-Arabian), 35,54,[73][74][75][76] have been defined in African SCD populations; however, these haplotypes are not predictive of HbF levels. We recently published data demonstrating that b-haplotypes generated using traditional methods such as restriction fragment length polymorphisms are insufficient to define the genomic structure in the HBB locus.…”
mentioning
confidence: 99%
“…Historically, five major b-haplotypes, including Senegal, Benin, Central African Republic (Bantu), Cameroon, and Asian (Indian/Saudi-Arabian), 35,54,[73][74][75][76] have been defined in African SCD populations; however, these haplotypes are not predictive of HbF levels. We recently published data demonstrating that b-haplotypes generated using traditional methods such as restriction fragment length polymorphisms are insufficient to define the genomic structure in the HBB locus.…”
mentioning
confidence: 99%
“…The Bantu and Benin haplotypes have been associated with low HbF levels and increased severity of clinical manifestations in sickle cell patients 3,35 compared with the Senegal and Arab-Indian haplotypes with higher HbF and a milder disease phenotype. 36,37 However, these haplotypes are not consistently predictive of clinical severity of SCA patients.…”
Section: Genomicsmentioning
confidence: 99%
“…These ratios are defined in more detail in this study as is shown in figure 2; homozygotes for haplotypes 3 or 31 have G γ values of 70–76%; those for type 19, 20, and for types 19 + 20 have G γ values of 36–53%, while compound heterozygotes for types 3 and 19 and for 3 and 20 have G γ levels from 54 to 73%, distinctly lower than the values for haplotype 3 homozygotes. The observed differences have been explained based on the presence or absence of the C→T mutation at position –158 ( G γ) (T for β S haplotypes 3 and 31; C for all others) [11, 14, 15, 16, 17]. The Mor haplotype appears to be unique: the 1 SS patient with a homozygosity for this haplotype has a G γ value of less than 20% and the 2 with the 19/Mor haplotype combination have values of 29.8 and 32.8%, intermediate between the values for patients with haplotypes 19/19 and Mor/Mor.…”
Section: Discussionmentioning
confidence: 99%